2018
DOI: 10.1007/s00277-018-3409-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and comorbidities on the efficacy of FC and FCR regimens in chronic lymphocytic leukemia

Abstract: CLL is an aging-associated neoplasm with median age at diagnosis > 65 years. Little is known about safety and efficacy of FC/FCR regimens in elderly CLL patients with multiple comorbidities. We retrospectively revised medical records of 90 patients treated with FC/FCR regimens in our clinic. Data on demographic and biological characteristics, comorbidities, response to therapy, and treatment-associated adverse events were analyzed. Compared to FC, FCR yielded higher rates of OR (93.6 vs. 81.4%, p = .109) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…At CLL diagnosis, some studies have reported that comorbidity associates with inferior overall survival (OS) (10,17,18) although in two studies associations did not withstand multifactorial modelling (9,11). Similar association between comorbidity and poorer OS and progression-free survival have been demonstrated from time of treatment in some studies (17,(19)(20)(21)(22), but not all studies replicate these findings (23,24). Increased mortality unrelated to CLL, both from time of diagnosis and after chemoimmunotherapy, has been described for comorbid patients (9,25), while comorbidity has not been correlated to CLL-related mortality (9).…”
Section: Introductionmentioning
confidence: 93%
“…At CLL diagnosis, some studies have reported that comorbidity associates with inferior overall survival (OS) (10,17,18) although in two studies associations did not withstand multifactorial modelling (9,11). Similar association between comorbidity and poorer OS and progression-free survival have been demonstrated from time of treatment in some studies (17,(19)(20)(21)(22), but not all studies replicate these findings (23,24). Increased mortality unrelated to CLL, both from time of diagnosis and after chemoimmunotherapy, has been described for comorbid patients (9,25), while comorbidity has not been correlated to CLL-related mortality (9).…”
Section: Introductionmentioning
confidence: 93%
“…Several retrospective analyses have investigated the impact of fitness status in terms of CIRS, renal impairment (CrCl < 70 mL/min), and ECOG PS in CLL patients that have undergone chemoimmunotherapy (CIT) [ 16 , 17 , 18 , 19 , 20 , 21 ]. For elderly/unfit CLL patients, direct and indirect comparisons have been made, mostly with the following regimens: fludarabine–cyclophosphamide +/− rituximab, bendamustine–rituximab, chlorambucil–rituximab, and ibrutinib.…”
Section: The Evaluation Of Patients’ Fitness Statusmentioning
confidence: 99%
“…For elderly/unfit CLL patients, direct and indirect comparisons have been made, mostly with the following regimens: fludarabine–cyclophosphamide +/− rituximab, bendamustine–rituximab, chlorambucil–rituximab, and ibrutinib. What emerged is that for patients that had undergone CIT, in most of them, neither older age nor higher ECOG PS had an impact on survival, while higher CIRS significantly worsened prognosis in almost all of them [ 16 , 17 , 18 , 19 ]. In only two studies, both investigating the use of bendamustine–rituximab in real life, a high ECOG PS showed a negative impact on survival in the Swedish group study in multivariate analysis (141 patients, of which 20% ECOG ≥ 2) [ 20 ], while in the GIMEMA-ERIC and US group study, only in univariate analysis (165 patients, of which 10% ECOG ≥ 2) [ 21 ].…”
Section: The Evaluation Of Patients’ Fitness Statusmentioning
confidence: 99%
“…The CIRS-G mechanism has previously been used to characterize disease burden and severity in elderly populations including those with cancer, [27][28][29][30][31][32][33][34][35][36][37][38][39] hip fracture, 40,41 those requiring hospitalization, [42][43][44][45] presenting to the emergency department, 46 and delirium. 47 Although much younger in chronological age, the use of this geriatric scale provides a robust approach for comparing the trajectory of aging among childhood cancer survivors, siblings, and the general population and did a reasonable job in predicting mortality over this study period (c-statistics, 0.67-0.86).…”
Section: Discussionmentioning
confidence: 99%